Analysis of the Needs of the Psychological Aspects of Rafting Athletes in West Java - Nasywa Nurul Fatonah; Yudha Munajat Saputra; Jajat (Universitas Negeri Semarang, 2026)
Rafting is an achievement sport that is carried out in the open air with a high level of risk, so it requires the physical, technical, and psychological readiness of athletes in facing environmental pressure and teamwork. However, the psychological aspect of rafting athletes has not been fully used as a basis for coaching, and studies that specifically discuss psychological needs in this extreme sport are relatively limited. This study aims to analyze the needs of the psychological aspects of rafting athletes in West Java as the basis for the development of more directed mental coaching. This study uses a quantitative descriptive design with a cross-sectional approach. The sample in this study involved 92 rafting athletes who were actively training and competing in West Java. The research instrument used was the Psychological Skills Inventory for Sports–Youth (PSIS-Y). The data were analyzed using descriptive statistics to describe the level of need of the psychological aspect of athletes. The results of the study showed that the motivation aspect was in the very high category with a percentage of 93.76%. The aspect of self-confidence (89.06%), and mental preparation (84.56%) are in the high category. Meanwhile, the aspects of team emphasis (69.92%), concentration (66.52%), and anxiety (60.14%) were in the medium category. These findings show that rafting athletes in West Java have different levels of psychological needs, with motivation, confidence and mental preparation being the most dominant psychological components. Therefore, improvements are needed in the management of team stress, anxiety, and concentration. The results of this research can be used as a basis for the preparation of mental coaching programs that are in accordance with the characteristics of rafting sports.